Cytoplasmic streaming in algae and root tips - IWF (IWF (Göttingen), 2005)
(en)Rotational streaming in the stonewort Nitella flexilis. Cytoplasmic streaming in the root tip of Limnobium stoloniferum. From the CD-ROM: BEREITER-HAHN, JÜRGEN (Frankfurt a. M.). The Cell I - Life from Light and Air (C 7100)